Crowdfunding: what factors influence your success? - Reis, Joana Sofia Batista dos (2016)
Financing got a new dimension with the emergence of Crowdfunding platforms, start-ups and small projects were able to be financed and new ideas got the chance to be developed. Throughout this dissertation it will be displayed several characteristics of both Crowdfunding as an alternative mean of financing and the platform in study, Indiegogo. In addition, the crucial topic that is discussed in the following chapters is what can influence positively and negatively the success of a Crowdfunding campaign and what can contribute to a higher funding percentage. Although Crowdfunding is still an upcoming topic since the financial crisis in 2008, and have already helped thousands of start-ups, small projects and non-for-profit ideas to be funded, the benefits Crowdfunding can provide to the society and the economic development are far away to be known. This dissertation is most relevant to future project creators and entrepreneurs that aim to obtain financing through alternative sources, as it provides advices that can be used in future.